Nusinersen in pediatric and adult patients with type III spinal muscular atrophy. Issue 8 (24th June 2021) - Pera, Maria Carmela; Coratti, Giorgia; Bovis, Francesca; Pane, Marika; Pasternak, Amy; Montes, Jacqueline; Sansone, Valeria A.; Dunaway Young, Sally; Duong, Tina; Messina, Sonia; Mizzoni, Irene; D'Amico, Adele; et al.
Abstract: Objective: We report longitudinal data from 144 type III SMA pediatric and adult patients treated with nusinersen as part of an international effort. Methods: Patients were assessed using Hammersmith Functional Motor Scale Expanded (HFMSE), Revised Upper Limb Module (RULM), and 6‐Minute Walk Test (6MWT) with a mean follow‐up of 1.83 years after nusinersen treatment. Results: Over 75% of the 144 patients had a 12‐month follow‐up. There was an increase in the mean scores from baseline to 12 months on both HFMSE (1.18 points, p = 0.004) and RULM scores (0.58 points, p = 0.014) but not on the 6MWT (mean difference = 6.65 m, p = 0.33). When the 12‐month HFMSE changes in the treated cohort were compared to an external cohort of untreated patients, in all untreated patients older than 7 years, the mean changes were always negative, while always positive in the treated ones. To reduce a selection bias, we also used a multivariable analysis. On the HFMSE scale, age, gender, baseline value, and functional status contributed significantly to the changes, while the number of SMN2 copies did not contribute. The effect of these variables was less obvious on the RULM and 6MWT. Interpretation: Our results expand the available data on the effect of Nusinersen on type III patients, so far mostly limited to data from adult type III patients.